Analisis Keterkaitan Sektor Tanaman Bahan Makanan dalam Perekonomian Wilayah Provinsi Jawa Barat (Studi Kasus Tahun 2003 dengan Analisis Input Output) - M. Enton Diyana; Emmy Saraswati; Neni Widayaningsih (EKO-REGIONAL, 2008)
The aim of this research are to study the backward and forward linkages of foodstuff plant sector towards another economic sector and to study how condition of supply and demand of commodity of foodstuff plant sector in West Java, 2003. The research method is descriptive one by using the data of Input Output (IO) Table of West Java, 2003, with 86 sectors in classification. The linkage analysis divides into the backward and forward linkages. The results of the research are foodstuff plant sector in West Java, 2003: (a) has backward linkage lower than forward one by looking at total value of backward linkage and also forward one; (b) has relation with 23 economic sectors in backward and 21 economic sectors in forward; and (c) can not cover all demand commodity of corn, sweet potatoes, soybean, and other foodstuff plant commodities. This results mean that to increase product of foodstuff plant especially commodity of corn, sweet potatoes, and soybean, it can do by increasing economic activities in forward, for examples food industry sector, restaurant sector, cultivation industry sector, etc. Keywords : backward linkage, forward linkage, input output analysis